Screening accuracy and clinical application of the Brief Infant-Toddler Social and Emotional Assessment (BITSEA). - Ingrid Kruizinga (Public Library of Science (PLoS), 2013)
Background The Brief Infant-Toddler Social and Emotional Assessment (BITSEA) is a promising questionnaire for the early detection of psychosocial problems in toddlers. The screening accuracy and clinical application were evaluated. Methods In a community sample of 2-year-olds (N = 2060), screening accuracy of the BITSEA Problem scale was examined regarding a clinical CBCL1.5-5 Total Problem score. For the total population and subgroups by child's gender and ethnicity Receiver Operating Characteristic (ROC) curves were calculated, and across a range of BITSEA Problem scores, sensitivity, specificity, likelihood ratio's, diagnostic odds ratio and Youden's index. Clinical application of the BITSEA was examined by evaluating the relation between the scale scores and the clinical decision of the child health professional. Results The area under the ROC curve (95% confidence interval) of the Problem scale was 0.97(0.95-0.98), there were no significant differences between subgroups. The association between clinical decision and BITSEA Problem score (B = 2.5) and Competence score (B = -0.7) was significant (p<0.05). Conclusions The results indicate that the BITSEA Problem scale has good discriminative power to differentiate children with and without psychosocial problems. Referred children had less favourable scores compared to children that were not referred. The BITSEA may be helpful in the early detection of psychosocial problems.